Peningkatan Pengetahuan Awam tentang Kondisi Psikologis Penyintas Bencana melalui Pelatihan Bantuan Psikologis Awal di Universitas YARSI - Octaviani Indrasari Ranakusuma; Sri Wuryanti; Ade Nursanti (Yayasan REDI Tiga Monas, 2023)
Indonesia is prone of earthquakes as it is located within ‘ring of fire’. Each disaster causes loss and grief which can lead to injuries and depression if untreated. Psychological First Aid (PFA) aims to reduce the initial distress of a traumatic event and to promote adaptive functioning and coping both in the short and long term. Trained laypersons are also able to provide psychological support which may reduce the stress experienced by survivors. Two-days Psychological First Aid training was conducted in Universitas YARSI with 36 participants consisted of students, lectures, and education-supporting staff to increase their awareness on physical and psychological state of post disaster survivors and to know when to refer to a professional. Pre- and Post-tests were conducted in 23 participants who attended the second day of training. A t-test demonstrated insignificant increase (t=1.95; p=.06) in participants’ knowledge on psychological states and in providing psychological support for survivors. The benefits and limitations of the training were discussed.